RESERCH STUDIES ON THE LOCATION OF A WAVE ENERGY POWER PLANT WITHIN CONSTANTA AREA - SAMOILESCU Gheorghe; RADU Serghei, Stena; DELIU Florenţiu; POPOV Petrică (Fiabilitate şi Durabilitate)
This paper is based on a research project on the development and installation of the first hydropneumatic plant in the Black Sea. It shows the location and its particularities, existing and previous hydrometeorological conditions, required work, plant qualities and standards to be met. The wave characteristics calculation and the hydrotechnic studies were presented: articulated concrete blocks demolition of the existing breakwater; dredging for the foundation of the plant; accomplish the foundation of the plant; installation of the plant; testing; consolidation and assuring protection of the breakwater; consolidation and assuring protection of the plant. Environmental protection measures are an important part of any research project of this type.